Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T20:09:42+01:00
A) 3(4x- 5y +6z) = 12x-15y+18z
b) -6(2a-3b+c) = -12a+18b-6c
c) ½(-8x +4y-2z) = -4x+2y-z
d)(-5a+b-3c)*(-4) = 20a-4b+12c
e)-⅓(12c+ 15d -21e) = -4c-5d+7e
f) -4(-3x² - y ² +5y ²) = 12x²+4y²-20y² = 12x²-16y²
2010-03-17T20:12:35+01:00
A) 3(4x- 5y +6z)=12x-15y+18z
b) -6(2a-3b+c)=-12a+18b-6c
c) 1 druga(-8x +4y-2z)=-4x+2y-z
d)(-5a+b-3c) razy (-4)=20a-4b+12c=
e)(-1 trzecia (12c+ 15d -21e)=-1/3*(12c+15d-21e)=-4c--5d+7e
f) -4(-3x2 - y2 +5y2)=12x2+4y2-20y2

licze na naj;)
2010-03-17T20:15:24+01:00
A) 3(4x-5y+6z)=12x-15y+18z
b) -6(2a-3b+c)=-12a+18b-6c
c) 1/2 (-8x+4y-2z)=-4x+2y-z
d) (-5a+b-3c)*(-4)=20a-4b+12c
e) -1/3(12c+15d-21e)=-4c-5d+7e
f) -4(-3x kwadrat - y kwadrat + 5y kwadrat=12x kwadrat +4y kwadrat -20y kwadrat = 12x kwadrat -16 y kwadrat